2016
DOI: 10.1145/2858652
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Hardware Message Passing for Efficient Thread Synchronization

Abstract: As the level of parallelism in manycore processors keeps increasing, providing efficient mechanisms for thread synchronization in concurrent programs is becoming a major concern. On cache-coherent shared-memory processors, synchronization efficiency is ultimately limited by the performance of the underlying cache coherence protocol. This paper studies how hardware support for message passing can improve synchronization performance. Considering the ubiquitous problem of mutual exclusion, we adapt two stateof-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In [16], we showed that on a processor provided with hardware message-passing support, such stalls on the server can be fully avoided. Reaching the same result in a cache-coherent sharedmemory system would probably require being able to specify the cache of a remote core where data should be placed, as proposed in [15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In [16], we showed that on a processor provided with hardware message-passing support, such stalls on the server can be fully avoided. Reaching the same result in a cache-coherent sharedmemory system would probably require being able to specify the cache of a remote core where data should be placed, as proposed in [15].…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, we have studied delegation in the context of a processor provided with support for message passing in hardware [16]. The results show that this feature can be used to significantly improve performance, mainly because RMRs on the server's critical path can be fully avoided.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations